LRP1 is a receptor for Clostridium perfringens TpeL toxin indicating a two-receptor model of clostridial glycosylating toxins - Schorch, Björn (National Academy of Sciences, 2014)
Large glycosylating toxins are major virulence factors of various species of pathogenic Clostridia. Prototypes are Clostridium difficile toxins A and B, which cause antibiotics-associated diarrhea and pseudomembranous colitis. The current model of the toxins’ action suggests that receptor binding is mediated by a C-terminal domain of combined repetitive oligopeptides (CROP). This model is challenged by the glycosylating Clostridium perfringens large cytotoxin (TpeL toxin) that is devoid of the CROP domain but still intoxicates cells. Using a haploid genetic screen, we identified LDL receptor-related protein 1 (LRP1) as a host cell receptor for the TpeL toxin. LRP1-deficient cells are not able to take up TpeL and are not intoxicated. Expression of cluster IV of LRP1 is sufficient to rescue toxin uptake in these cells. By plasmon resonance spectroscopy, a K(D) value of 23 nM was determined for binding of TpeL to LRP1 cluster IV. The C terminus of TpeL (residues 1335–1779) represents the receptor-binding domain (RBD) of the toxin. RBD-like regions are conserved in all other clostridial glycosylating toxins preceding their CROP domain. CROP-deficient C. difficile toxin B is toxic to cells, depending on the RBD-like region (residues 1349–1811) but does not interact with LRP1. Our data indicate the presence of a second, CROP-independent receptor-binding domain in clostridial glycosylating toxins and suggest a two-receptor model for the cellular uptake of clostridial glycosylating toxins.